Lunisolar tidal force and its relationship to chlorophyll fluorescence in Arabidopsis thaliana - Fisahn, Joachim (Plant Signal Behav, 2015)
The yield of chlorophyll fluorescence Ft was measured in leaves of Arabidopsis thaliana over periods of several days under conditions of continuous illumination (LL) without the application of saturating light pulses. After linearization of the time series of the chlorophyll fluorescence yield (ΔFt), oscillations became apparent with periodicities in the circatidal range. Alignments of these linearized time series ΔFt with the lunisolar tidal acceleration revealed high degrees of synchrony and phase congruence. Similar congruence with the lunisolar tide was obtained with the linearized quantum yield of PSII (ΔФII), recorded after application of saturating light pulses. These findings strongly suggest that there is an exogenous timekeeper which is a stimulus for the oscillations detected in both the linearized yield of chlorophyll fluorescence (ΔFt) and the linearized quantum yield of PSII (ΔФII).